Stunting Prevention in Indonesia Between 2018-2023 from Scopus: A Bibliometric Study - Putri, Selviana Azzira; Yuadi, Imam (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2025)
Stunting remains a significant concern, particularly in Indonesia. This study aims to assess the development of scientific publications related to stunting prevention in the country. A bibliometric analysis method was utilized to identify research trends concerning stunting prevention in Indonesia. Data were collected from the Scopus database and processed using Biblioshiny software from R-Studio. The results indicate a steady increase in publications on stunting prevention in Indonesia from 2018 to 2023, suggesting a rise in research activity during this period. Future research topics may include the relationship between malnutrition and children in Indonesia, poverty, being small for gestational age, immunization, and attitudes toward health.  Keywords: Bibliometric, biblioshiny, indonesia, stunting prevention